A Case of Large Meningeal Epithelioid Hemangioendothelioma With WWTR1–CAMTA1 Gene Rearrangement and Slow Growth Over 15 Years. Issue 10 (10th July 2018) - Süß, Patrick; Volz, Florian; Lang, Christine; Staszewksi, Ori; Palmedo, Gabriele; Taschner, Christian A; Scheiwe, Christian; Kurz, Philipp; Mentzel, Thomas; Prinz, Marco
Abstract: Epithelioid hemangioendothelioma (EHE) is a rare vascular neoplasm predominantly occurring in the soft tissue. A majority of EHE cases is driven by a WW domain containing transcription regulator protein 1 ( WWTR1 )— calmodulin-binding transcription activator 1 ( CAMTA1 ) gene fusion. The clinical course of EHE ranges from long-term favorable to rapidly aggressive. Few cases of intracranial EHE have been reported, none of which has been molecularly proven. We report a case of left parietal meningeal EHE, which was resected 15 years after initial radiological detection. Four years prior to surgery, a second atlantooccipital lesion and pulmonary nodules were detected, which remained constant in subsequent radiological controls. The tumor infiltrated the cranial bone. Histology showed an isomorphic tumor with epithelioid cells forming vacuoles that contained erythrocytes. Necrosis was absent and anaplasia and proliferative activity were scant. Immunohistochemistry showed expression of the endothelial markers CD34, CD31, vascular endothelial growth factor, and factor VIII and predominantly nuclear overexpression of CAMTA1. Fluorescence in situ hybridization showed WWTR1–CAMTA1 gene fusion. Our report provides the first case of intracranial EHE with molecular proof of WWTR1–CAMTA1 gene fusion. The slowly progressive clinical course of 15 years is the longest so far reported for intracranial EHE.